EFFICACY OF INTRANASAL ESKETAMINE AS A NOVEL RAPID ANTIDEPRESSANT IN ADULTS WITH TREATMENT- RESISTANT DEPRESSION - Eldy Eldy; Aurielle Annalicia Setiawan; Sartika Sabhinaya; Pedro Arruda Supinto; Teddy Tjahyanto (Universitas Pahlawan, 2023)
Major depressive disorder (MDD), the leading cause of disability worldwide is a common and disabling mental health disorder associated with high suicide-related morbidity and mortality rates. Despite the availability of antidepressant therapies, one-third of patients with MDD fail to achieve remission and are considered to have Treatment-Resistant Depression (TRD). Research have found intranasal esketamine, an enantiomer of anesthetic drug called ketamine, as a potential breakthrough in combating treatment resistance and lowering the number of depression-related suicides. However, reviews that cover the potential use of esketamine are still limited. This review aims to summarize the study of esketamine and provide a better insight into its efficacy and safety in TRD patients as a promising end point for TRD remission. Literature sources were taken from journal articles published in the last five years. The databases used were PMC, SAGE Journals, ScienceDirect, Wiley, and ResearchGate. TRD is associated with impaired social functioning and imminent risk of suicidal ideation. The antidepressant effect of intranasal esketamine showed a noteworthy result varying from increased response rate to decreased depression symptoms and suicidal thoughts. Findings from clinical trials indicate that intranasal esketamine is effective and safe in patients with TRD. It implies that esketamine has rapid antidepressant effects in patients with MDD, including TRD and MDSI. Further research regarding esketamine efficacy in some populations such as pediatrics and people with a history of psychosis, is still needed to improve our ability to treat TRD.